2002
DOI: 10.1590/s0004-28032002000100008
|View full text |Cite
|
Sign up to set email alerts
|

Study of morbidity in orthotopic small intestine transplantation with Wistar rats: experimental study

Abstract: The experimented intestinal transplant is a procedure companied by considerable morbidity and mortality due to surgical complications in postoperative period, vascular anastomosis and total surgical time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…The success rate found in this study was 83.3%, which is comparable to those from literature. are also within the range reported in literature (15 to 25min 7,12 ; 45 to 67min 6,10,11 , 25min 9 and 113 to 120min 9,11 , respectively). Mean donor operation time in this study (40min) is shorter than found in others studies (57 12 , 81 11 and 89min 9 ).…”
Section: Clinical Indication Of Intestinal Transplantation Hassupporting
confidence: 90%
See 2 more Smart Citations
“…The success rate found in this study was 83.3%, which is comparable to those from literature. are also within the range reported in literature (15 to 25min 7,12 ; 45 to 67min 6,10,11 , 25min 9 and 113 to 120min 9,11 , respectively). Mean donor operation time in this study (40min) is shorter than found in others studies (57 12 , 81 11 and 89min 9 ).…”
Section: Clinical Indication Of Intestinal Transplantation Hassupporting
confidence: 90%
“…Although the varied outcome of rejection in outbred rats may be comparable to that observed in outbred large animals, including humans, these results demonstrate the unpredictability of long-term immunological response in transplantation models using outbred rats. In a previous report of our group 6 , we observed 41.1% (7 out of 17) of 30 days post-operative survival. These widely variable results corroborate the unpredictability of outbred rats long-term evolution.…”
Section: Clinical Indication Of Intestinal Transplantation Hassupporting
confidence: 44%
See 1 more Smart Citation
“…In agreement with Lee et al, arterial anastomosis bleeding was the most common intra-operative complication in the recipient [5]. A successful vascular anastomosis is achieved following the microsurgery principles recommended by Guity et al [24].…”
Section: Discussionsupporting
confidence: 65%
“…In general terms, it is used to study intestinal ischemia-reperfusion injury, graft rejection and assess immunosuppressive therapies [2][3][4]. SBTx in rats is a feasible, replicable and inexpensive procedure when compared to large animals models [5].…”
Section: Introductionmentioning
confidence: 99%